Solving the lignin waste crisis: Utilization of lignin to produce value- added antioxidant agents: حل أزمة نفايات اللجنين: استخدام اللجنين لإنتاج مضادات أكسدة ذات قيمة مضافة - Feras Mosleh Almowalad (Journal of engineering sciences and information technology, 2021)
Lignin is a major component of biomass that is considered a huge energy and carbon reserve. Aside from being the second most abundant polymer in nature, it is a major by- product of pulping, paper and other forestry- based industries with about 70 million tons per year. Due to it being highly biologically recalcitrant, lignin is underutilized and considered a waste product that is solely incinerated for power generation. Establishment of a market for lignin- based, value- added chemicals was a necessity. Because of its renewable nature, availability, and richness in phenolic component, however, it is considered as an attractive alternative for antioxidant activity. In our research, all types of extracted lignin exhibited a value ranging from 2.21 to 11.47 on the AAI assay suggesting high antioxidant activity. Furthermore, special chemical structures such as hydrogen atoms, double bonds between side chain carbons, as well as the presence of methoxyl groups can increase antioxidant activity by 2- 3 folds via means of radical scavenging. Finally, lignin extracted at higher temperature ( 95C and greater) exhibited higher ORAC values compared to lignin extracted at lower temperature; ORAC values of 1072.32 to 3119.68 versus 1741.72 to 1745.11, respectively. This paper is going to shed more light on the lignin antioxidant properties, where it stems from, what affects it, as well as future directions and possible interdisciplinary potential improvement.